The Transformatioin of Jengki Style Public Buildings in Surabaya - Audina, Shafira Zulfa (Universitas Muhammadiyah Surakarta, 2025)
Architecture in Indonesia began to experience a vibrant growth in the years following independence and the post-independence war, which became the emergence of jengki architecture. Jengki is an architectural style that characterized by eccentric shapes; gavel walls, gables, roosters, sloping columns, and a concrete creation with unusual shapes. Emerging in the late 1950s, jengki style has expanded all over Indonesia, including Surabaya. Jengki style buildings in Surabaya are not only residential, but also public buildings that are rarely known. Public buildings are places for the communities to do activities and interact socially, forming a collective memory that is part of urban life. The existence of jengki style public buildings is slowly fading and disappearing from the city's face and replaced by modern buildings. This article discusses the transformation of three jengki style public buildings in Surabaya, which is Khadijah School Hall, Wonokromo Market, and Gelora Pancasila. All three of them underwent different transformation and treatment. Using a qualitative study with a historical paradigm, it employed archival tracking tactics and building documentation in three timelines. Furthermore, the analysis shows that economic factors and the need for modernization are the reasons for the jengki disappearance. Different treatment of buildings also has an impact on the survival of jengki buildings. For this reason, it requires particular approaches to maintain the jengki style as well as the preservation process of Gelora Pancasila conducted by the Surabaya City Government.